Scientific and practical aspects of airport activities management mechanism formation within the framework of the Eurasian Economic Union - T. M. Gainochenko (Управление)
The article analyses the current practice of economic regulation of airport activities of the member states of the Eurasian Economic Union (EAEU). The author concludes, that the demand management tools available to the air transport market entities of the EAEU member states are limited. In order to eliminate this limitation, the paper proposes the idea of an integrated information management platform for marketing management in public-private partnership with a shift in focus towards the demand for transport services. The study formulates the main tasks, that such a platform should solve, as follows: 1) managing the flight schedule of airlines and the work of railway and bus operators at the airports of the EAEU member states; 2) the management of a database on the demand for air transport services from tourist operators, as well as enterprises involved in the organization and holding of exhibitions, conferences, cultural events; 3) the management of an integrated system for offering air transport services for cargo and mail delivery. The paper gives recommendations for the formation of a single transport space of the EAEU member states through a digital decision-making system for assessing the economic potential of airports. In the course of the study, the author clarifies the concepts of "natural monopoly" and "competitive market".